2009
DOI: 10.1074/jbc.m808463200
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin-2 Mediates Anti-apoptotic Signaling through Regulation of BAD Phosphorylation

Abstract: ␤-Arrestins, originally discovered as terminators of G protein-coupled receptor signaling, have more recently been appreciated to also function as signal transducers in their own right, although the consequences for cellular physiology have not been well understood. Here we demonstrate that ␤-arrestin-2 mediates anti-apoptotic cytoprotective signaling stimulated by a typical 7-transmembrane receptor the angiotensin ATII 1A receptor, expressed endogenously in rat vascular smooth muscle cells or by transfection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 50 publications
3
112
2
1
Order By: Relevance
“…However, SII-mediated ERK phosphorylation is graded and slow with localization of phosphorylated ERK (pERK) in the cytoplasm (11). AngII activates apoptotic signals while SII activates anti-apoptotic ones (12). Great efforts have been made to identify unique signaling pathways of -arrestin-biased agonists.…”
Section: Introductionmentioning
confidence: 99%
“…However, SII-mediated ERK phosphorylation is graded and slow with localization of phosphorylated ERK (pERK) in the cytoplasm (11). AngII activates apoptotic signals while SII activates anti-apoptotic ones (12). Great efforts have been made to identify unique signaling pathways of -arrestin-biased agonists.…”
Section: Introductionmentioning
confidence: 99%
“…12,13) Ex vivo studies further revealed that SII treatment had positive inotropic and lusitropic effects in cardiomyocytes isolated from wildtype mice but not in cardiomyocytes from β-arrestin2 deficient mice. 14) Consistent with the previous in vitro studies, SII was able to activate MAPK in perfused hearts.…”
Section: Physiological Consequences Of At1r-β-arrestin Signaling In Tmentioning
confidence: 99%
“…13) To examine whether AT1R-β-arrestin signaling triggered by mechanical stretch acts as a prosurvival signal, hearts isolated from wild-type mice, AT1aR-deficient mice and β-arrestin2-deficient mice were subjected to balloon stretch ex vivo. Mechanical stretch resulted in Akt phosphorylation in wild-type hearts but not in AT1aR-deficient hearts or in β-arrestin2-deficient hearts.…”
Section: Physiological Consequences Of At1r-β-arrestin Signaling In Tmentioning
confidence: 99%
“…Intriguingly, recent studies demonstrate that in VSMCs, arrestin 2 mediates AGTR1-dependent prevention of apoptosis and is required for both LPA and thrombin-induced vascular smooth muscle cell proliferation (Ahn et al, 2009;Kim et al, 2008). Furthermore, deficiency of arrestin 2 protects LDL receptor knockout (ldlr -/-) mice from aortic atherosclerosis (Kim et al, 2008).…”
Section: Upstream Targetsmentioning
confidence: 99%